Analisis Pengaruh Efektivitas E-Performance terhadap Kinerja Aparatur Sipil Negara (ASN) - Sari, Putri Melinda; Anisykurlillah, Rosyidatuzzahro (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2025)
This study aims to examine the effectiveness of e-performance implementation on the performance of the State Civil Apparatus (ASN) at the Surabaya City Transportation Agency. The focus of the problem lies in the effectiveness of e-performance and ASN performance at the Surabaya City Transportation Agency. This quantitative research employs the Effectiveness variable (X) as an independent variable, referring to Duncan's theory (1973). The employee performance variable (Y), as the dependent variable, refers to the theoretical approach of Bernardin (2012). This study employed a quantitative methodology, collecting data via questionnaires and documentation. The population comprised 236 State Civil Apparatus from the Surabaya City Transportation Agency, with a sample of 142 respondents determined based on the Issac and Michael table. The results show that the effectiveness of the application of e-performance has a positive and significant influence on the performance of ASN at the Surabaya City Transportation Agency. The results of the t-test show that the significance value is 0.000 (p < 0.05), and the t-count is 14.565 (t-count> t-table 1.977). The coefficient of determination test yields an R-squared value of 0.602. That indicates that the variable effectiveness of e-performance implementation can explain and contribute an influence of 60.2% to the ASN performance variable.